From Protection to Repression: State Containment of COVID-19 Pandemic and Human Rights Violations in Nigeria - Ezeibe, Christian Chukwuebuka (Victims & offenders, 2024)
While previous studies have assessed the linkages between the implementation of the coronavirus disease 2019 (COVID-19) lockdown and human rights issues in non-African contexts, how the state containment of COVID-19 pandemic affected human rights in African context has been understudied, particularly in Nigeria. Using a qualitative-dominant mixed methods approach, this study assessed how state containment of COVID-19 pandemic affected human rights in Nigeria. It demonstrated that the state’s security operatives repressed the citizens during the implementation of COVID-19-induced full and partial lockdown in Nigeria. Despite the prospects of COVID-19 lockdown in mitigating the spread of the virus, state repression of citizens has implications for shrinking the civic spaces and engendering human rights violations. The study concluded that judicial reform and promotion of rights-based education among security operatives involved in the implementation of COVID-19 lockdown present opportunities for regulating the excesses of the state officials during public health emergencies, preserving human rights as well as advancing democracy and development in Nigeria.